CHALKING UP THE BENEFITS' PROJECT: THE ECONOMIC VALUATION OF ECOSYSTEM SERVICE IN LEWES, EAST SUSSEX, ENGLAND - Wulandari, Wulandari (Jurnal Ekonomi & Studi Pembangunan, 2019)
The economic valuation of ecosystem services has promoted awareness from within the society to both the ecological and economic consequences of biodiversity loss. This has emerged with reference to the debate about its usefulness. This study, however, reviewed the concept of ecosystem services as a discourse within its metaphor about human dependence on the natural world. Some literature, reports or strategic plans, historical archives and websites were reviewed to conduct the sociopolitical analysis of the institutionalization of the concept in the prior review. It depicts specifically the context of the local communities’ movement to value the natural capital at the Lewes area, East Sussex, England as part of the programs to decouple ‘green payment’ from agricultural sector. Based on the collected evidences, this research argues, there have been a similar pattern of the institutional settings towards the environmental protections between changes related to agricultural pressures and urban pressures. Finally, it can be concluded that, the discourse of ecosystem services using the economic valuation process has also been shaped by the elite capture.